TLR4 modulates simvastatin’s impact on HDL cholesterol and glycemic control - Tian, Xiao; Zhang, Peixiang (Frontiers in Pharmacology, 2026)
BackgroundStatins reduce atherosclerotic cardiovascular risk by inhibiting HMG-CoA reductase and lowering LDL cholesterol, but their efficacy and adverse effects—particularly statin-associated dysglycemia—are tightly coupled to sterol regulatory element-binding protein (SREBP)–regulated cholesterol biosynthesis. Emerging work indicates that feeding–fasting cycles, rather than intrinsic circadian clocks, are the dominant drivers of hepatic SREBP activity and de novo lipogenesis. In parallel, the “feeding state” is now recognized to include metabolic endotoxemia, whereby gut-derived lipopolysaccharide (LPS) enters the circulation and activates Toll-like receptor 4 (TLR4), impinging on SREBP, liver X receptor (LXR), and peroxisome proliferator-activated receptor-α (PPARα) signaling. How this LPS–TLR4 axis interacts with statin action to shape lipid and glucose metabolism remains unknown.MethodsWe leveraged the natural diurnal rhythm of food intake in mice to test how simvastatin timing relative to fasting–feeding cycles and LPS–TLR4 signaling influences metabolic outcomes. Simvastatin was administered either during the fasting (rest) phase by oral gavage or during the active feeding phase via chow admixture. Comprehensive metabolic phenotyping was integrated with hepatic transcriptomics and biochemical assays to interrogate SREBP-2–mediated autophagy, LXR/SREBP-1c activity, and PPARα signaling. To define the contribution of metabolic endotoxemia, parallel studies were performed in Tlr4-deficient mice.ResultsIn wild-type mice, fasting-phase simvastatin activated SREBP-2–dependent autophagy, augmented PPARα signaling, and increased HDL cholesterol but impaired glucose homeostasis. In contrast, feeding-phase simvastatin lowered HDL cholesterol while improving glucose tolerance and insulin sensitivity. Mechanistically, feeding elicited a surge in circulating LPS that suppressed hepatic oxysterol production, sensitizing the liver to further simvastatin-mediated oxysterol depletion and attenuation of LXR/SREBP-1c activity, thereby shifting the LXR/SREBP-1c/PPARα axis toward reduced HDL biogenesis and enhanced glycemic control. TLR4 deficiency abolished these feeding-phase effects, reversing the HDL-lowering and glucose-improving actions of simvastatin.ConclusionThe timing of simvastatin administration relative to feeding versus fasting exerts opposing effects on HDL and glucose metabolism, and these divergent outcomes are critically gated by feeding-induced LPS–TLR4 signaling. Aligning statin therapy with nutritional state, and potentially targeting the LPS–TLR4–SREBP/LXR/PPARα axis, may offer a tractable strategy to optimize lipid-lowering efficacy while mitigating dysglycemic risk.